Implementation of Classic Management Theory in the Distribution of Duties and Authority in State Primary Schools 57/Ix Muaro Jambi - Muhammad Yamin; Anaswan (International Journal of Educational and Life Sciences, 2025)
Based on the researcher's grand tour of the Muaro Jambi 57/IX Public Elementary School, it was found that first, management implementation was not in line with the division of duties and authority of teachers. Second, the principal only fulfills his obligations without exceeding limits. Third, the organization of time, work tools and facilities is not yet optimal. This qualitative research uses a qualitative case approach. The subjects of this research are elementary school principals. Data collection uses observation, interview and documentation techniques. Data analysis uses the Miles and Huberman model which includes data reduction, data presentation, and data withdrawal. The research results show that job satisfaction provides a clear sign in producing the Implementation of Classical Management Theory in the Division of Duties and Authority at the 57/IX Muaro Jambi State Elementary School. The feeling of satisfaction or happiness felt by the teacher has an impact on the quality of the performance provided. Teacher competency, which is reflected in the division of work, is clearly an important factor in producing job satisfaction which leads to the quality of performance produced. For leaders, it is very important to pay attention to job satisfaction in the division of tasks and authority in order to create high quality performance by increasing the competency of human resources (teachers) which is reflected in the division of work in accordance with the areas of expertise or abilities of human resources (teachers).